Indonesian Monetary Crisis in 1998 Impact, Casues and How to Overcome - Relawanto, Nugroho Setiyo (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The Indonesian exchange rate crisis in 1997/1998 caused a very sharp decline in the exchange rate, thereby increasing the burden of foreign debt which was dominated by private companies and high inflation in Indonesia.. The aim of this research is to determine and analyze the exchange rate crisis in Indonesia in 1998, which includes the monetary situation before, during and after the monetary crisis, the impact of the monetary crisis, the causes of the monetary crisis and how to overcome the monetary crisis. The type and source of data uses a secondary data approach in the form of documentary data in various media around 1998.